DISKRIMINASI PENDIDIKAN DI INDONESIA: ANALISIS TEORI DEMOKRASI PENDIDIKAN ISLAM - Indah, Astrid Veranita (Universitas Islam Negeri Alauddin Makassar, 2020)
Education is the formation of human character that leads to individual independence. An individual is able to develop the potential of self-reliance and quality of resources through the democratization of education. Democratizing education requires an adequate teaching and learning tool, but in a pandemic condition a conducive learning atmosphere is impossible to achieve. Education will undergo significant changes when faced with a new situation that is different from the constant rhythm of life of Indonesian society.This study is a qualitative research literature. The researchers will choose between primary sources and secondary sources; classifying the data; then presenting the data. While the method of analysis using the method of philosophical hermeneutics, which starts with a description, interpretation, historical continuity, and heuristics.Democracy of education creates the creativity of students in increasing intellectual, spiritual intelligence, and developing skills in themselves that are in accordance with the conditions of social society. The aim of democratization education is to provide equal rights for each individual to develop their potential and gain knowledge. Intellectual development is based on empathy, sympathy, and creativity. With the democracy of education, every individual has equal rights in acquiring knowledge in the midst of a pandemic Covid-19. Democracy of education also avoid someone has the mindset to control and dominate the other.